Material advancement in tissue-engineered nerve conduit - Dai Wufei (De Gruyter, 2021)
Peripheral nerve injuries resulting from various traumatic events can cause mobility problems and sensory impairment, jeopardizing patients’ life quality and bringing serious economic burdens. Due to the shortcomings of autologous nerve grafts, such as limited tissue sources, unmatched size, and loss of innervation at the donor site, tissue-engineered nerve grafts using both natural and synthetic materials have been employed in the treatment of peripheral nerve defect and to promote nerve regeneration. Apart from traditional advantages such as good biocompatibility and controllable degradation, the development of fabrication technology and the advancement in material science have endowed tissue-engineered nerve conduits with upgraded properties such as biomimetic surface topography, extracellular matrix components, neurotrophic factors, and cell seeding, or a conduit with micropores on the surface for substance exchange and/or with fillers inside for microenvironment simulation. This article reviews recent progress in the biomaterials employed in fabricating tissue-engineered nerve conduits, in vitro characterization, and their applications in nerve repair in animal studies as well as in clinical trials.